Bridging the gap in patent assessment: The Index of Internal Effort framework for pharma innovations - Alisson A. de Oliveira; Celso B. dos Santos; Luiz A. Pilatti (GarVal Editorial Ltda., 2024)
Context: The process of assessing patents is complex, and there is a gap in the literature on patent assessment at the time of filing. Aims: To assess patent complexity and the human effort involved in research, we test the effectiveness of the Index of Internal Effort (IIE) framework using pharmaceutical patents developed within the Brazilian public sector as a proof of concept. Methods: Internal data were collected from innovation projects that included the filing of patents as a project outcome. The Spearman correlation test was applied to determine which internal patent variables could be used as metrics in IIE. Then, IIE was used to measure the complexity of the patents and the individual effort of inventors. Results were then compared with other metrics identified in the literature. Results: The IIE showed a positive and significant correlation with resources invested at the design stage, as well as commercial and social outcomes of the patents. Conclusions: The results indicate that the generic IIE framework is a new form of metrification that can be applied to pharmaceutical patents that have not been previously discussed in the literature.